Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To solve the given summation problem when [tex]\( n = 6 \)[/tex], we need to evaluate two separate summations and then combine them according to the expression given. Specifically, we need to compute:
[tex]\[ 3 \sum_{k=1}^n (2k-3) + \sum_{k=1}^n (4-5k) \][/tex]
Let's break this down into two parts and evaluate them step-by-step.
### Step 1: Evaluate [tex]\(\sum_{k=1}^n (2k-3)\)[/tex]
We need to find the sum of the sequence [tex]\(2k - 3\)[/tex] from [tex]\( k = 1 \)[/tex] to [tex]\( k = 6 \)[/tex]:
[tex]\[ \sum_{k=1}^6 (2k-3) = (2 \cdot 1 - 3) + (2 \cdot 2 - 3) + (2 \cdot 3 - 3) + (2 \cdot 4 - 3) + (2 \cdot 5 - 3) + (2 \cdot 6 - 3) \][/tex]
Calculating each term individually:
[tex]\[ = (2 \cdot 1 - 3) + (2 \cdot 2 - 3) + (2 \cdot 3 - 3) + (2 \cdot 4 - 3) + (2 \cdot 5 - 3) + (2 \cdot 6 - 3) \][/tex]
[tex]\[ = (2 - 3) + (4 - 3) + (6 - 3) + (8 - 3) + (10 - 3) + (12 - 3) \][/tex]
[tex]\[ = -1 + 1 + 3 + 5 + 7 + 9 \][/tex]
Adding these results:
[tex]\[ -1 + 1 = 0 \][/tex]
[tex]\[ 0 + 3 = 3 \][/tex]
[tex]\[ 3 + 5 = 8 \][/tex]
[tex]\[ 8 + 7 = 15 \][/tex]
[tex]\[ 15 + 9 = 24 \][/tex]
Therefore, [tex]\(\sum_{k=1}^6 (2k-3) = 24\)[/tex].
### Step 2: Evaluate [tex]\(\sum_{k=1}^n (4-5k)\)[/tex]
Next, we need to find the sum of the sequence [tex]\(4 - 5k\)[/tex] from [tex]\( k = 1 \)[/tex] to [tex]\( k = 6 \)[/tex]:
[tex]\[ \sum_{k=1}^6 (4-5k) = (4 - 5 \cdot 1) + (4 - 5 \cdot 2) + (4 - 5 \cdot 3) + (4 - 5 \cdot 4) + (4 - 5 \cdot 5) + (4 - 5 \cdot 6) \][/tex]
Calculating each term individually:
[tex]\[ = (4 - 5 \cdot 1) + (4 - 5 \cdot 2) + (4 - 5 \cdot 3) + (4 - 5 \cdot 4) + (4 - 5 \cdot 5) + (4 - 5 \cdot 6) \][/tex]
[tex]\[ = (4 - 5) + (4 - 10) + (4 - 15) + (4 - 20) + (4 - 25) + (4 - 30) \][/tex]
[tex]\[ = -1 - 6 - 11 - 16 - 21 - 26 \][/tex]
Adding these results:
[tex]\[ -1 - 6 = -7 \][/tex]
[tex]\[ -7 - 11 = -18 \][/tex]
[tex]\[ -18 - 16 = -34 \][/tex]
[tex]\[ -34 - 21 = -55 \][/tex]
[tex]\[ -55 - 26 = -81 \][/tex]
Therefore, [tex]\(\sum_{k=1}^6 (4-5k) = -81\)[/tex].
### Step 3: Combine the Results
Now we combine the results with the given constants:
[tex]\[ 3 \cdot \sum_{k=1}^6 (2k-3) + \sum_{k=1}^6 (4-5k) \][/tex]
Substituting the results we obtained:
[tex]\[ 3 \cdot 24 + (-81) \][/tex]
[tex]\[ 72 - 81 \][/tex]
[tex]\[ = -9 \][/tex]
### Final Answer
Therefore, the value of the given summation when [tex]\( n = 6 \)[/tex] is:
[tex]\[ -9 \][/tex]
[tex]\[ 3 \sum_{k=1}^n (2k-3) + \sum_{k=1}^n (4-5k) \][/tex]
Let's break this down into two parts and evaluate them step-by-step.
### Step 1: Evaluate [tex]\(\sum_{k=1}^n (2k-3)\)[/tex]
We need to find the sum of the sequence [tex]\(2k - 3\)[/tex] from [tex]\( k = 1 \)[/tex] to [tex]\( k = 6 \)[/tex]:
[tex]\[ \sum_{k=1}^6 (2k-3) = (2 \cdot 1 - 3) + (2 \cdot 2 - 3) + (2 \cdot 3 - 3) + (2 \cdot 4 - 3) + (2 \cdot 5 - 3) + (2 \cdot 6 - 3) \][/tex]
Calculating each term individually:
[tex]\[ = (2 \cdot 1 - 3) + (2 \cdot 2 - 3) + (2 \cdot 3 - 3) + (2 \cdot 4 - 3) + (2 \cdot 5 - 3) + (2 \cdot 6 - 3) \][/tex]
[tex]\[ = (2 - 3) + (4 - 3) + (6 - 3) + (8 - 3) + (10 - 3) + (12 - 3) \][/tex]
[tex]\[ = -1 + 1 + 3 + 5 + 7 + 9 \][/tex]
Adding these results:
[tex]\[ -1 + 1 = 0 \][/tex]
[tex]\[ 0 + 3 = 3 \][/tex]
[tex]\[ 3 + 5 = 8 \][/tex]
[tex]\[ 8 + 7 = 15 \][/tex]
[tex]\[ 15 + 9 = 24 \][/tex]
Therefore, [tex]\(\sum_{k=1}^6 (2k-3) = 24\)[/tex].
### Step 2: Evaluate [tex]\(\sum_{k=1}^n (4-5k)\)[/tex]
Next, we need to find the sum of the sequence [tex]\(4 - 5k\)[/tex] from [tex]\( k = 1 \)[/tex] to [tex]\( k = 6 \)[/tex]:
[tex]\[ \sum_{k=1}^6 (4-5k) = (4 - 5 \cdot 1) + (4 - 5 \cdot 2) + (4 - 5 \cdot 3) + (4 - 5 \cdot 4) + (4 - 5 \cdot 5) + (4 - 5 \cdot 6) \][/tex]
Calculating each term individually:
[tex]\[ = (4 - 5 \cdot 1) + (4 - 5 \cdot 2) + (4 - 5 \cdot 3) + (4 - 5 \cdot 4) + (4 - 5 \cdot 5) + (4 - 5 \cdot 6) \][/tex]
[tex]\[ = (4 - 5) + (4 - 10) + (4 - 15) + (4 - 20) + (4 - 25) + (4 - 30) \][/tex]
[tex]\[ = -1 - 6 - 11 - 16 - 21 - 26 \][/tex]
Adding these results:
[tex]\[ -1 - 6 = -7 \][/tex]
[tex]\[ -7 - 11 = -18 \][/tex]
[tex]\[ -18 - 16 = -34 \][/tex]
[tex]\[ -34 - 21 = -55 \][/tex]
[tex]\[ -55 - 26 = -81 \][/tex]
Therefore, [tex]\(\sum_{k=1}^6 (4-5k) = -81\)[/tex].
### Step 3: Combine the Results
Now we combine the results with the given constants:
[tex]\[ 3 \cdot \sum_{k=1}^6 (2k-3) + \sum_{k=1}^6 (4-5k) \][/tex]
Substituting the results we obtained:
[tex]\[ 3 \cdot 24 + (-81) \][/tex]
[tex]\[ 72 - 81 \][/tex]
[tex]\[ = -9 \][/tex]
### Final Answer
Therefore, the value of the given summation when [tex]\( n = 6 \)[/tex] is:
[tex]\[ -9 \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.